2017
DOI: 10.1002/mp.12010
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous fluoroscopic and nuclear imaging: impact of collimator choice on nuclear image quality

Abstract: A real-time hybrid fluoroscopic and nuclear imaging device is currently being developed. Image quality of nuclear images obtained with different collimators was compared in terms of contrast, noise, and detectability. Parallel hole collimators showed lower noise and better detectability than pinhole collimators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The authors propose a hybrid imaging system, consisting of an X-ray c-arm combined with gamma imaging capabilities for simultaneous real-time fluoroscopic and nuclear imaging. A slightly modified version of this prototype [ 123 ] was shown to be able to accurately estimate LSF of a 99m Tc-MAA scout dose in an interventional setting [ 124 ]. When this hybrid imaging modality becomes available in the angiography room, it may be possible to move towards 1-day procedures by combining scout and therapy dose in one session.…”
Section: Reviewmentioning
confidence: 99%
“…The authors propose a hybrid imaging system, consisting of an X-ray c-arm combined with gamma imaging capabilities for simultaneous real-time fluoroscopic and nuclear imaging. A slightly modified version of this prototype [ 123 ] was shown to be able to accurately estimate LSF of a 99m Tc-MAA scout dose in an interventional setting [ 124 ]. When this hybrid imaging modality becomes available in the angiography room, it may be possible to move towards 1-day procedures by combining scout and therapy dose in one session.…”
Section: Reviewmentioning
confidence: 99%
“…Our hybrid imaging device is extensively described and evaluated for physical performance earlier (Beijst et al 2015, van der Velden et al 2017, including the hardware and algorithms that are applied to generate a real time, simultaneous hybrid planar image. In short, four gamma cameras are symmetrically placed around the x-ray tube, hence creating stereoscopic views of the FOV without blocking the line of sight of the x-ray modality (figure 1) (Beijst et al 2015).…”
Section: Device Designmentioning
confidence: 99%
“…To this end, a real-time, simultaneous fluoroscopic and nuclear imaging device is currently being developed by our group, consisting of a c-arm combined with four gamma cameras (figure 1) (Beijst et al 2015, van der Velden et al 2017. This set-up enables simultaneous acquisition of fluoroscopic and nuclear images of the same field-of-view (FOV), thereby creating overlapping hybrid images in both the spatial and the temporal domain.…”
Section: Introductionmentioning
confidence: 99%
“…In the design of Beijst et al (2) and van der Velden et al (3), four g cameras with pinhole collimators were positioned at the side of the x-ray tube. Although the prototype showed that interventional hybrid imaging was feasible, this design required an intermediate reconstruction step and additional weight added to the already heavy x-ray tube.…”
mentioning
confidence: 99%